Galleys of freedom - Francisco Herrera-Rodríguez (Universidad de Alicante, 2017)
This brief text is a tribute to Juan Peña El Lebrijano. The 'cantaor' was born in Lebrija in August 1941 and died in Seville in July 2016. He knew how to combine tradition and innovation, and sang as nobody the lyrics of Félix Grande and Gabriel García Márquez.